FERTILIZER RECOMMENDATION BASED ON SOIL TESTING FOR THE TARGETED YIELD OF RICE IN EASTERN PLAIN ZONE OF UTTER PRADESH - REGAR, KANHAIYA LAL; Y. V. SINGH, (The Bioscan, 2014)
A field experiment was conducted on rice crop under soil test crop response correlation studies in Varanasi region of Utter Pradesh during kharif 2011. Multiple regressions have been calibrated for predicting rice yield through soil and fertilizer nutrients and their interactions. The models were found to have a high and significant predictability value. Using the data, fertilizer adjustment equations have also been developed for prescribing optimum fertilizer doses for attaining different yield targets. The nutrient requirements (kg q•1) of N, P2O5 and K2O for producing one quintal of rice yield in Inceptisol were found to be 2.56, 0.56 and 2.21, respectively. The per cent contributions of nutrient from soil, fertilizers and FYM were 26.35, 51.17 and 26.14; 54.03, 36.35 and 75.68; and 18.59, 3.10 and 8.56 of N, P and K nutrients, respectively. The fertilizer adjustment equations and a ready reckoner of optimum fertilizer doses at varying soil test values for attaining yield target of 40 and 50 q ha-1 of rice yield have been calibrated based on the targeted yield concept.